A high-strength and good-appearance polyamide composite material and its preparation method and application

By rationally formulating polyamide and metal salt compounds and using the compatible agent polycarbodiimine, the problem of difficult to take into account the appearance quality while improving strength, achieving both high strength and good appearance, and is suitable for a variety of high-performance injection molded products.

CN118027665BActive Publication Date: 2025-04-04ORINKO ADVANCED PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410227269.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2025-04-04
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

While the existing polyamide composite materials increase strength, they are difficult to take into account both the appearance quality, resulting in the problems of floating fiber and low gloss.

Method used

By reasonably formulating semi-crystalline polyamide, non-crystalline polyamide and metal salt compounds, and using the compatible agent polycarbodiimide, the fluidity and dispersion of carbon fiber in polyamide are improved, the appearance is improved, and mechanical properties are improved.

Benefits of technology

It achieves a balance of high strength and good appearance, and is suitable for injection-molded products in the fields of automobiles, electronic devices, power tools and sports equipment that require high mechanical properties and excellent appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004720089620000091
    Figure BDA0004720089620000091
  • Figure BDA0004720089620000101
    Figure BDA0004720089620000101
Patent Text Reader

Abstract

The present invention provides a high-strength and good-appearance polyamide composite material and its preparation method and application, which relate to the technical field of polymer materials. A high-strength and good-appearance polyamide composite material comprises the following raw materials in parts by weight: 32.5-72.5 parts of semi-crystalline polyamide, 5-15 parts of non-crystalline polyamide, 20-50 parts of carbon fiber, 0.5-2 parts of compatibilizer, 0.5-1.5 parts of metal salt compound, 0.2-0.5 parts of antioxidant and 0.2-0.5 parts of lubricant. After adding metal salt compound and compatibilizer polycarbodiimide to the polyamide material, due to the positive effect of metal salt compound on appearance state and the positive effect of compatibilizer polycarbodiimide on mechanical properties, the polyamide composite material can maintain high strength while showing a good appearance state. The high-strength and good-appearance polyamide composite material provided by the present invention can be applied to injection molded products in the fields of automobiles, electronic devices, electric tools, sports equipment, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-strength and good-appearance polyamide composite material and a preparation method and application thereof. Background Art

[0002] Polyamide is an engineering material with excellent performance, which has the advantages of high strength and excellent heat resistance, wear resistance, chemical resistance, heat and oxygen aging resistance and good processability. With the development and progress of society, the use environment faced by polyamide is becoming more and more harsh, and the requirements for strength are getting higher and higher. In order to meet this demand, carbon fiber is usually added to obtain higher strength and rigidity. However, when too much carbon fiber is added, due to the poor compatibility between carbon fiber and polyamide, and the high content of carbon fiber is easy to leak on the surface of the product, the appearance of the molded product produced by this modified material is relatively poor, and there are obvious floating fibers and low gloss. At present, the industry generally solves the problem of floating fibers in appearance by using a polyamide resin with a lower viscosity or adding a highly branched compound to improve the processing fluidity of polyamide to improve the fluidity of the composition, or adopts special additives that reduce the crystallization temperature of polyamide and adjusts the extrusion process to obtain excellent appearance. Although these solutions can improve the appearance of the modified material to a certain extent, there is a certain sacrifice in the mechanical properties of the material, resulting in the product's strength and appearance cannot be taken into account at the same time. Therefore, there is an urgent need to develop a high-strength and good-appearance polyamide composite material, which is of great significance for its application in the fields of automobiles, electronic devices, power tools and sports equipment. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a high-strength and good-appearance polyamide composite material and a preparation method and application thereof.

[0004] The invention provides a high-strength and good-appearance polyamide composite material, which comprises the following raw materials in parts by weight: 32.5 to 72.5 parts of semi-crystalline polyamide, 5 to 15 parts of non-crystalline polyamide, 20 to 50 parts of carbon fiber, 0.5 to 2 parts of a compatibilizer, 0.5 to 1.5 parts of a metal salt compound, 0.2 to 0.5 parts of an antioxidant and 0.2 to 0.5 parts of a lubricant.

[0005] Preferably, the semi-crystalline polyamide is selected from at least one of PA6, PA11, PA12, PA46, PA56, PA66, PA610, PA612, PA1010, PA1212, PA6T, PA9T, and PA10T; more preferably PA66.

[0006] Preferably, the non-crystalline polyamide is selected from at least one of PA6I, PA 6I / 6T, PA MXDI / 6I, PA MXDI / 12I, PA MXDI, PA MXDI / MXD6, PA MACM10, PA MACM12, PA MACM14, and PAMACM18; more preferably PA6I.

[0007] Preferably, the carbon fiber is selected from at least one of polyacrylonitrile-based carbon fiber, viscose fiber carbon fiber and pitch fiber carbon fiber.

[0008] Preferably, the compatibilizer is selected from at least one of aliphatic, alicyclic and aromatic polycarbodiimide.

[0009] Preferably, the metal salt compound is selected from at least one of lithium chloride, calcium chloride, potassium chloride, zinc chloride, copper chloride, lithium bromide, calcium bromide, potassium bromide, zinc bromide, copper bromide, lithium iodide, calcium iodide, potassium iodide, zinc iodide and copper iodide.

[0010] Preferably, the antioxidant is selected from at least one of hindered phenol antioxidants, thioether antioxidants and phosphite antioxidants.

[0011] More preferably, the hindered phenol antioxidant is selected from at least one of antioxidant 1098 and antioxidant 1010; the thioether antioxidant is selected from at least one of antioxidant DSTP and antioxidant DLTP; the phosphite antioxidant is selected from at least one of antioxidant 168 and antioxidant S-9228.

[0012] Preferably, the lubricant is at least one of ethylene bis stearamide, pentaerythritol stearate and silicone masterbatch.

[0013] The present invention also provides a method for preparing a high-strength and good-appearance polyamide composite material, comprising the following steps:

[0014] S1, drying the semi-crystalline polyamide and the non-crystalline polyamide;

[0015] S2, after uniformly mixing the metal salt compound, the compatibilizer, the lubricant and the antioxidant, adding the semi-crystalline polyamide and the non-crystalline polyamide treated in S1 and mixing them uniformly to obtain a mixed material;

[0016] S3, the mixed material in S2 and the carbon fiber are melted, extruded, granulated, water-cooled, blow-dried and then pelletized to obtain a high-strength and good-appearance polyamide composite material.

[0017] Preferably, in S1, the drying temperature is 100-120° C., and the drying time is 3-4 hours.

[0018] The present invention also proposes an application of the high-strength and good-appearance polyamide composite material in injection molded products in the fields of automobiles, electronic devices, electric tools and sports equipment.

[0019] The beneficial effects of the present invention are:

[0020] The present invention uses semi-crystalline polyamide and non-crystalline polyamide in combination with metal salt compounds to help slow down the crystallization speed of polyamide and reduce the crystallinity of polyamide, thereby improving the fluidity and dispersibility of carbon fiber in polyamide and obtaining a good appearance. At the same time, the compatibilizer polycarbodiimide is used to improve the bonding effect between carbon fiber and polyamide resin matrix, thereby improving the mechanical properties of the composite material. The high-strength and good-appearance polyamide composite material of the present invention has high strength and excellent appearance, is suitable for preparing lightweight thin-walled molded products by injection molding, and is applied to injection molded products in the fields of automobiles, electronic devices, electric tools, sports equipment, etc. that require good appearance and high requirements for material mechanical properties. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is described in detail through specific embodiments.

[0022] In the following examples and comparative examples, the specific information of the raw materials used is as follows:

[0023] Semi-crystalline polyamide PA66: Manufacturer: Huafeng Group; Brand: EP158;

[0024] Non-crystalline polyamide PA6I: Manufacturer: Shandong Guangyin;

[0025] Aromatic polycarbodiimide: Manufacturer: Rheinland, Germany; Brand: Stabaxol P;

[0026] Polyacrylonitrile-based carbon fiber: Manufacturer: Japan Toray; Brand: T700;

[0027] Lithium chloride: manufacturer: Shanghai Zhongli; calcium chloride: manufacturer: Qiren Chemical; potassium chloride: manufacturer: Aladdin; zinc chloride: manufacturer: Hengfeng Zinc Industry;

[0028] Antioxidant 1098: Manufacturer: Lianlong; Brand: 1098; Antioxidant S-9228: Manufacturer: Dover, USA; Brand: S-9228;

[0029] Ethylene bisstearamide: Manufacturer: Kao, Japan;

[0030] Silicone masterbatch: Manufacturer: Dow Corning; Brand: MB50-001;

[0031] Pentaerythritol stearate: Manufacturer: Italy Faji.

[0032] Example 1

[0033] A high-strength and good-appearance polyamide composite material comprises the following raw materials in parts by weight: 72.5 parts of semi-crystalline polyamide PA66, 5 parts of non-crystalline polyamide PA6I, 20 parts of polyacrylonitrile-based carbon fiber, 0.5 parts of aromatic polycarbodiimide, 1.5 parts of lithium chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.5 parts of ethylene bisstearamide.

[0034] A method for preparing a high-strength and good-appearance polyamide composite material comprises the following steps:

[0035] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0036] S2, adding lithium chloride, aromatic polycarbodiimide, ethylene bisstearamide, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated in S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0037] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and after melting, extrusion, and granulation, water cooling, blow drying and pelletizing, a high-strength and good-appearance polyamide composite material is obtained, wherein the nine-zone processing temperatures of the twin-screw extruder are: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0038] Example 2

[0039] A high-strength and good-appearance polyamide composite material comprises the following raw materials in parts by weight: 58 parts of semi-crystalline polyamide PA66, 10 parts of non-crystalline polyamide PA6I, 30 parts of polyacrylonitrile-based carbon fiber, 1 part of aromatic polycarbodiimide, 1 part of calcium chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.5 parts of silicone masterbatch.

[0040] A method for preparing a high-strength and good-appearance polyamide composite material comprises the following steps:

[0041] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0042] S2, adding calcium chloride, aromatic polycarbodiimide, silicone masterbatch, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into a high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0043] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and after melting, extrusion, and granulation, water cooling, blow drying and pelletizing, a high-strength and good-appearance polyamide composite material is obtained, wherein the nine-zone processing temperatures of the twin-screw extruder are: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0044] Example 3

[0045] A high-strength and good-appearance polyamide composite material comprises the following raw materials in parts by weight: 47.5 parts of semi-crystalline polyamide PA66, 10 parts of non-crystalline polyamide PA6I, 40 parts of polyacrylonitrile-based carbon fiber, 1.5 parts of aromatic polycarbodiimide, 1.5 parts of potassium chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.2 parts of pentaerythritol stearate.

[0046] A method for preparing a high-strength and good-appearance polyamide composite material comprises the following steps:

[0047] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0048] S2, adding potassium chloride, aromatic polycarbodiimide, pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0049] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and after melting, extrusion, and granulation, water cooling, blow drying and pelletizing, a high-strength and good-appearance polyamide composite material is obtained, wherein the nine-zone processing temperatures of the twin-screw extruder are: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0050] Example 4

[0051] A high-strength and good-appearance polyamide composite material comprises the following raw materials in parts by weight: 32.5 parts of semi-crystalline polyamide PA66, 15 parts of non-crystalline polyamide PA6I, 50 parts of polyacrylonitrile-based carbon fiber, 2 parts of aromatic polycarbodiimide, 0.5 parts of zinc chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.5 parts of pentaerythritol stearate.

[0052] A method for preparing a high-strength and good-appearance polyamide composite material comprises the following steps:

[0053] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0054] S2, adding zinc chloride, aromatic polycarbodiimide, pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0055] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and after melting, extrusion, and granulation, water cooling, blow drying and pelletizing, a high-strength and good-appearance polyamide composite material is obtained, wherein the nine-zone processing temperatures of the twin-screw extruder are: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0056] Comparative Example 1

[0057] A polyamide composite material comprises the following raw materials in parts by weight: 60 parts of semi-crystalline polyamide PA66, 10 parts of non-crystalline polyamide PA6I, 30 parts of polyacrylonitrile-based carbon fiber, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.2 parts of pentaerythritol stearate.

[0058] A method for preparing a polyamide composite material comprises the following steps:

[0059] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0060] S2, adding pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0061] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and obtain a polyamide composite material after melting, extrusion, granulation, water cooling, blow drying and pelletizing, wherein the nine-zone processing temperatures of the twin-screw extruder are as follows: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0062] Comparative Example 2

[0063] A polyamide composite material comprises the following raw materials in parts by weight: 59 parts of semi-crystalline polyamide PA66, 10 parts of non-crystalline polyamide PA6I, 30 parts of polyacrylonitrile-based carbon fiber, 1 part of potassium chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.5 parts of pentaerythritol stearate.

[0064] A method for preparing a polyamide composite material comprises the following steps:

[0065] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0066] S2, adding potassium chloride, pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0067] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and obtain a polyamide composite material after melting, extrusion, granulation, water cooling, blow drying and pelletizing, wherein the nine-zone processing temperatures of the twin-screw extruder are as follows: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0068] Comparative Example 3

[0069] A polyamide composite material comprises the following raw materials in parts by weight: 59 parts of semi-crystalline polyamide PA66, 10 parts of non-crystalline polyamide PA6I, 30 parts of polyacrylonitrile-based carbon fiber, 1 part of aromatic polycarbodiimide, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.2 parts of pentaerythritol stearate.

[0070] A method for preparing a polyamide composite material comprises the following steps:

[0071] S1, drying the semi-crystalline polyamide PA66 and the non-crystalline polyamide PA6I at 110°C for 4 hours;

[0072] S2, adding aromatic polycarbodiimide, pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 and non-crystalline polyamide PA6I treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0073] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and obtain a polyamide composite material after melting, extrusion, granulation, water cooling, blow drying and pelletizing, wherein the nine-zone processing temperatures of the twin-screw extruder are as follows: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0074] Comparative Example 4

[0075] A polyamide composite material comprises the following raw materials in parts by weight: 68 parts of semi-crystalline polyamide PA66, 30 parts of polyacrylonitrile-based carbon fibers, 1 part of aromatic polycarbodiimide, 1 part of calcium chloride, 0.2 parts of antioxidant 1098, 0.3 parts of antioxidant S-9228 and 0.2 parts of pentaerythritol stearate.

[0076] A method for preparing a polyamide composite material comprises the following steps:

[0077] S1, drying the semi-crystalline polyamide PA66 at 110°C for 4h;

[0078] S2, adding calcium chloride, aromatic polycarbodiimide, pentaerythritol stearate, antioxidant 1098, and antioxidant S-9228 into a high-speed mixer and mixing at 1500 r / min for 3 min, adding the semi-crystalline polyamide PA66 treated by S1 into the high-speed mixer and mixing at 1500 r / min for 8 min to obtain a mixed material;

[0079] S3. Add the mixed material in S2 from the main feeding port of the twin-screw extruder, add the polyacrylonitrile-based carbon fiber from the side feeding port of the twin-screw extruder, and obtain a polyamide composite material after melting, extrusion, granulation, water cooling, blow drying and pelletizing, wherein the nine-zone processing temperatures of the twin-screw extruder are as follows: the temperature of zones 1 and 2 is 250-270°C, the temperature of zones 3 to 7 is 240-260°C, the temperature of zones 8 and 9 is 250-270°C, the head temperature is 270-280°C, and the screw speed is 400rpm.

[0080] The polyamide composite materials prepared in the above Examples 1 to 4 and Comparative Examples 1 to 4 were tested for density, tensile strength, flexural strength, flexural modulus, and notched impact strength according to relevant testing standards, and their appearance was visually observed. The performance test data results are shown in Table 1.

[0081] Table 1 Related properties of polyamide composite materials in examples and comparative examples

[0082]

[0083]

[0084] Note: In Table 1, * indicates the appearance quality, and the more *, the better the appearance;

[0085] It can be seen from the data of Examples 1 to 4 that as the content of polyacrylonitrile-based carbon fiber increases, the mechanical properties of the polyamide composite material increase, but when the content of polyacrylonitrile-based carbon fiber is too high, the appearance state will slightly decrease. When the content of polyacrylonitrile-based carbon fiber added to the polyamide composite material system is 30 parts, it has better mechanical properties and appearance. It can be seen from the data of Comparative Example 1 and Example 2 that without adding metal salt compounds and compatibilizer polycarbodiimide to the polyamide composite material system, the mechanical properties of the polyamide composite material are reduced and the product appearance is poor; it can be seen from the data of Comparative Example 2, Example 2 and Comparative Example 1 that without adding compatibilizer polycarbodiimide to the polyamide composite material system, the mechanical properties of the polyamide composite material are further reduced, but compared with Comparative Example 1, a metal salt compound is added to Comparative Example 2, and the appearance of the polyamide composite material is significantly improved; it can be seen from the data of Comparative Example 3, Example 2 and Comparative Example 1 that without adding metal salt compounds to the polyamide composite material system, the product appearance is poor, but compared with Comparative Example 1, a compatibilizer polycarbodiimide is added to Comparative Example 3, and the mechanical properties of the polyamide composite material are significantly improved; it can be seen from the data of Comparative Example 4 and Example 2 that without adding amorphous polyamide to the polyamide composite material system, the mechanical properties of the polyamide composite material do not change much, but the product appearance is average.

[0086] In summary, the high-strength and good-appearance polyamide composite material provided by the present invention is obtained by adding a metal salt compound and a compatibilizer polycarbodiimide to a polyamide material, so that the polyamide composite material can maintain high strength while showing a good appearance. The high-strength and good-appearance polyamide composite material provided by the present invention can be applied to injection molded products in the fields of automobiles, electronic devices, electric tools, sports equipment, etc.

[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-strength and good-appearance polyamide composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 32.5 to 72.5 parts of semi-crystalline polyamide, 5 to 15 parts of non-crystalline polyamide, 20 to 50 parts of carbon fiber, 0.5 to 2 parts of a compatibilizer, 0.5 to 1.5 parts of a metal salt compound, 0.2 to 0.5 parts of an antioxidant and 0.2 to 0.5 parts of a lubricant; the compatibilizer is an aromatic polycarbodiimide; and the metal salt compound is selected from at least one of lithium chloride, calcium chloride, potassium chloride and zinc chloride.

2. A high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The semi-crystalline polyamide is selected from at least one of PA6, PA11, PA12, PA46, PA56, PA66, PA610, PA612, PA1010, PA1212, PA6T, PA9T, and PA10T.

3. The high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The non-crystalline polyamide is selected from at least one of PA6I, PA 6I / 6T, PAMXDI / 6I, PAMXDI / 12I, PAMXDI, PAMXDI / MXD6, PAMACM10, PAMACM12, PAMACM14, and PA MACM18.

4. The high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The carbon fiber is selected from at least one of polyacrylonitrile-based carbon fiber, viscose fiber carbon fiber and asphalt fiber carbon fiber.

5. The high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The antioxidant is selected from at least one of hindered phenol antioxidants, thioether antioxidants and phosphite antioxidants.

6. The high-strength and good-appearance polyamide composite material according to claim 1, characterized in that: The lubricant is at least one of ethylene bis stearic acid amide, pentaerythritol stearate and silicone masterbatch.

7. The method for preparing a high-strength and good-appearance polyamide composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, drying the semi-crystalline polyamide and the non-crystalline polyamide; S2, after uniformly mixing the metal salt compound, the compatibilizer, the lubricant and the antioxidant, adding the semi-crystalline polyamide and the non-crystalline polyamide treated in S1 and mixing them uniformly to obtain a mixed material; S3, the mixed material in S2 and the carbon fiber are melted, extruded, granulated, water-cooled, blow-dried and then pelletized to obtain a high-strength and good-appearance polyamide composite material.

8. Use of a high-strength and good-appearance polyamide composite material as claimed in any one of claims 1 to 6 in injection-molded products in the fields of automobiles, electronic devices, electric tools and sports equipment.

Citation Information

Patent Citations

  • Fibre-reinforced compound material core and preparation method thereof

    CN102602083A

  • Polyamide composition as well as preparation method and application thereof

    CN116622225A